2000
DOI: 10.1063/1.870309
|View full text |Cite
|
Sign up to set email alerts
|

Density ratio dependence of Rayleigh–Taylor mixing for sustained and impulsive acceleration histories

Abstract: The turbulent Rayleigh–Taylor instability is investigated over a comprehensive range of fluid density ratio (R)1.3⩽R⩽50 [0.15⩽A=(R−1)/(R+1)⩽0.96] and different acceleration histories g(t) using the Linear Electric Motor. The mixing layer is diagnosed with backlit photography and laser-induced fluorescence. For a constant acceleration, the bubble (2) and spike (1) amplitudes are found to increase as hi=αiAgt2 with α2∼0.05±0.005 and α1∼α2RDα with Dα∼0.33±0.05. For temporally varying accelerations Ag(t)>0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
294
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(332 citation statements)
references
References 64 publications
35
294
2
1
Order By: Relevance
“…Furthermore, with reference to Equation (2.3), the values of the growth exponent computed by the non-linear regression (NLR) analysis are summarised and compared against published results in Table 2. The growth exponent in the compressible simulation is found to be in good agreement with both the experiments of Dimonte and Schneider (2000) and the numerical simulations of Thornber et al (2010). Excellent agreement is also found with Youngs (2004), where θ = 0.243 was obtained from a long-time compressible simulation; the difference between Youngs (2004) and our simulations is approximately 0.001.…”
Section: Growth Of the Instabilitysupporting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, with reference to Equation (2.3), the values of the growth exponent computed by the non-linear regression (NLR) analysis are summarised and compared against published results in Table 2. The growth exponent in the compressible simulation is found to be in good agreement with both the experiments of Dimonte and Schneider (2000) and the numerical simulations of Thornber et al (2010). Excellent agreement is also found with Youngs (2004), where θ = 0.243 was obtained from a long-time compressible simulation; the difference between Youngs (2004) and our simulations is approximately 0.001.…”
Section: Growth Of the Instabilitysupporting
confidence: 76%
“…Experiments (Dimonte and Schneider 2000) confirmed the results giving an exponent for the formula (2.7) of 0.21 ± 0.05. Studying separately the evolution of bubble and spikes, the authors found that θ b is substantially independent from the Atwood number and has a value of 0.25 ± 0.05, whereas the spikes exponent has a very similar value to θ b only for A t < 0.8.…”
Section: Experiments and Numerical Simulationssupporting
confidence: 74%
See 1 more Smart Citation
“…More recently, experiments have been performed [5,6] with several deliberately chosen time-dependent s t g ) ' ( . These experimental profiles for ) (t g will form our starting point.…”
Section: Introduction Motivation and Notationmentioning
confidence: 99%
“…The three dimensional model predictions were compared to the Linear Electric Motor (LEM) experimental results presented by Dimonte & Schneider [4], with good agreement for the scaling parameters α b,s and h b / λ . However, the experiments did not provide a direct measurement of the bubble front size distribution due to their 3D nature, and the models validity in this manner was not confirmed.…”
Section: Introductionmentioning
confidence: 99%